A Systematic Review of Educational Interventions to Improve Self-Care Behaviors in Hypertensive Patients - Ni Ketut Erawati; I Gede Putu Darma Suyasa; I Kadek Nuryanto; Ni Made Manik Elisa Putri (Babali Nursing Research, 2025)
Introduction: Hypertension remains one of the most prevalent non-communicable diseases worldwide, including in Indonesia. Due to its often asymptomatic nature, the condition is frequently neglected by patients, increasing the risk of complications and negatively impacting their quality of life. While pharmacological treatment is essential, hypertension management is closely tied to self-care practices, which remain a persistent challenge. One strategy to improve self-care behavior in hypertensive patients is through education. This study aims to systematically review the effectiveness of various educational interventions in enhancing self-care behavior among hypertensive patients.Methods: This study employed the PRISMA Flowchart for article selection across three databases—ScienceDirect, PubMed, and Google Scholar—with inclusion criteria limited to articles published between 2021 and 2025. Of 394 initially identified articles, 15 met the inclusion criteria after PRISMA-based screening.Results: The review analyzed 15 studies comprising diverse educational interventions, including group-based education sessions, video-assisted learning, digital and mobile health (mHealth) tools, individualized counseling, and community-based programs. These interventions significantly improved key aspects of self-care, such as medication adherence, dietary regulation, physical activity, stress management, and regular blood pressure monitoring.Conclusion: This systematic review demonstrates that a wide range of educational interventions effectively enhance self-care behaviors among hypertensive patients. Tailoring interventions to patient needs and utilizing technology may further improve outcomes. These findings underscore the importance of incorporating structured education into hypertension management strategies.